THE RELATIONSHIP BETWEEN PROTEIN INTAKE, FAT INTAKE, AND SATISFACTION WITH FOOD PROVISION AND THE NUTRITIONAL STATUS OF STUDENTS AT HUSAINIYAH ISLAMIC BOARDING SCHOOL, CICALENGKA - Afani, Syifa Qolbi; Santanu, Ayu Mutiara; Insani, Hurry Mega; Astuti, Widya (Jurnal Gizi dan Pangan Soedirman, 2025)
Students at Husainiyah Islamic Boarding School in Cicalengka rely entirely on meals provided within a closed environment, making their nutrient intake and meal satisfaction important factors that may influence their nutritional status. This study aimed to analyze the association between protein and fat intake, as well as satisfaction with meal services, and the students’ nutritional status. This research used a quantitative method with a cross-sectional design, involving 60 students aged 12–18 years selected through total sampling. Dietary intake of protein and fat was assessed using two-day 24-hour food recall, while satisfaction levels were measured using a Likert scale. Nutritional status was evaluated based on BMI-for-age. Data were analyzed using the chi-square test. Findings showed that 30% of participants had inadequate protein intake, and 41.7% had insufficient fat intake, although 73.3% of them had a normal nutritional status. Half of the students expressed satisfaction with the meal service, while the other half were dissatisfied. The statistical analysis indicated a significant relationship (p-value<0.05) between protein and fat intake and nutritional status. However, satisfaction with meal services was not significantly associated with nutritional status. In conclusion, intake of protein and fat significantly correlates with nutritional status, while satisfaction does not.